1975
DOI: 10.1111/j.1346-8138.1975.tb00945.x
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Anti‐cytoplasmic Antibodies in a Case of Incontinentia Pigmenti

Abstract: Antibodies against the cytoplasm of normal human epidermal cells were found in both a newborn baby with incontinentia pigmenti and in her normal mother. These antibodies showed no tissue or species specificity as in the case of anti‐nuclear antibodies in SLE. The antibodies were assayed by indirect immunofluorescence. The antibody titer in the serum of the baby gradually decreased over a period of months while the mother's titer remained high. The generalized vesiculo‐bullous eruption noted at birth subsided w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
1989
1989

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…This distinction is obvious in this work. It is supported by the fact that several workers have reported *basal cell antibodies' (Thivolet & Beyvin, 1968;Van Joost, 1974;Ackerman Schopf er a/., 1974;Bystryn, 1976;Ackerman Schopf, 1976;Ablin, i976;Shmunes& Shu, 1977) or'upper'cell antibodies (Bystryn et al., 1973;Burnham, 1974;Ogawa et al., 1975;Abel & Bystryn, 1976). This means that each compartment has, in its cytoplasm, components which diifer in their antigenic properties (as far as we can assume from an immunofluorescent picture that the target antigens are actually in the cytoplasm).…”
Section: (I) Distinction Between Basal and Upper Compartmentsmentioning
confidence: 93%
“…This distinction is obvious in this work. It is supported by the fact that several workers have reported *basal cell antibodies' (Thivolet & Beyvin, 1968;Van Joost, 1974;Ackerman Schopf er a/., 1974;Bystryn, 1976;Ackerman Schopf, 1976;Ablin, i976;Shmunes& Shu, 1977) or'upper'cell antibodies (Bystryn et al., 1973;Burnham, 1974;Ogawa et al., 1975;Abel & Bystryn, 1976). This means that each compartment has, in its cytoplasm, components which diifer in their antigenic properties (as far as we can assume from an immunofluorescent picture that the target antigens are actually in the cytoplasm).…”
Section: (I) Distinction Between Basal and Upper Compartmentsmentioning
confidence: 93%
“…Increased mast cell numbers (16), high content of histamine (17) and of elevated serum IgE (18) have been reported in IP. On the other hand, Ogawa et al (19) found anti-cytoplasmic antibodies of normal human epidermal cells in both a newborn baby with IP and her normal mother. They suggested that the production of epidermal cell-derived ECF was generated by immune complexes in the lesions.…”
Section: Resultsmentioning
confidence: 98%